Assessment of Water-salt regime of Irrigation system - Assel Abdibay; Kanat Anuarbekov; Nurzhan Mukhamadiyev; Gulnaz Mengdibayeva (Caspian Journal of Environmental Sciences)
The main source of water for irrigation of agricultural crops in the Shieli area is the Syrdarya River. The main part of the river water intake originates in the Tomenaryk town through the trunk channel New Shieli. Through this channel, agricultural land in Akmaya, Kodamanov, Begezhanov, Zhuantobe, Bestam and other farms is irrigated. Through the Kamystyayak channel, farms in villages Bidaykol and Jahaev are irrigated. Through pipes located in irrigated areas, groundwater level and salinity indicator were identified. The ameliorative condition of the irrigated land in farms was considered unsatisfactory only in certain farming lands, due to their lowland and highland location, a change was noticed in soil mechanical composition. Soil salinity index depends on mineralization of irrigation water and groundwater. In the autumn of this year, a rapid drop of the groundwater level has been observed. This was caused by the fact that the water level of the Syrdarya River was lower, and the groundwater level in irrigated land dropped rapidly. To optimize this issue, the article presents the current state of irrigated lands in the lower reaches of the Syrdarya River in Kyzylorda province, as well as the results of work on regulation of water-salt regime. For this purpose, research work was conducted on 71.15 ha of agricultural land Bidaikol (former Giant), belonging to the Zhanakorgan-Shieli irrigation massif. According to the results of the research, it was optimal to provide the fields with water through a specially prepared biofield planted with dense reed plants. It was proved that purified irrigation water from the biofield is effective for irrigation of fodder crops. In addition, the reed itself is widely used in the republic as a fodder crop. Young reeds collected in August (at this time the reeds will be soft and the leaves green) are finely chopped and stored with a press using a special technology. Due to the growing importance of winter fodder, the price of reeds has increased significantly in the southern and southwestern regions of the country. For example, this year the price of 1 press of cane fluctuated between 650-850 tenge. In addition, this spring there was a shortage of fodder in the western regions (Aktau, Mangistau). Taking into account all these problems that the work done in the article is very relevant and more effective.